IMPROVEMENT OF MEANS FOR MECHANICAL THERAPY OF THE LOWER LIMBS - Neverov, Evgeny Nikolaevich; Plotnikov, Konstantin Borisovich; Plotnikov, Igor Borisovich; Neverova, Tatyana Vladimirovna; Yakovlev, Sergey Vladimirovich (Medicine in Kuzbass, 2026)
In modern trauma and orthopaedic practice, the role of post-operative rehabilitation as a distinct clinical phase is steadily increasing. However, early mobilisation of the ankle joint – a proven method for preventing contractures and joint fibrosis – remains difficult to achieve: an analysis of commercially available CPM devices has shown that the average weight of these devices exceeds 12 kg, and the vast majority of designs are intended exclusively for use in a ‘seated’ position, which precludes their use in the acute postoperative period when strict bed rest is required. The aim of the study is to develop and validate the architecture of a compact, passive-action mechanotherapy device free from the aforementioned limitations. Materials and methods. The work was carried out using a systematic approach integrating biomechanical analysis of ankle joint movements, the synthesis of multi-link kinematic schemes using methods from the theory of mechanisms and machines, finite element analysis of load-bearing components, and topological optimisation of the design. The load-bearing components were manufactured using the fused deposition modelling (FDM) method from a carbon-fibre-reinforced PETG composite (PETG-CF). Results. A prototype device for passive mechanotherapy of the ankle joint has been designed and manufactured. The proposed multi-link kinematic scheme with a variable instantaneous centre of rotation reproduces foot movements within a plantar flexion range of 0-40° and dorsiflexion range of 0-20°, with a trajectory error of no more than 2.5°. The use of additive manufacturing and topological optimisation has reduced the total weight of the device to 5 kg with dimensions of 400 × 350 × 450 mm. The modular design allows rehabilitation sessions to be conducted in both a «sitting» and «lying» position. Conclusion. The developed device fills the functional gap between bulky stationary CPM machines and wearable exoskeletons for active walking, enabling early passive mobilisation directly at the patient’s bedside. A multi-level overload protection system and the ability to programme individual protocols create the conditions for clinical testing of the device in both inpatient and outpatient rehabilitation settings.